Estimating abortion incidence and unintended pregnancy among adolescents in Zimbabwe, 2016: a cross-sectional study. Issue 4 (28th April 2020) - Riley, Taylor; Madziyire, Mugove G.; Chipato, Tsungai; Sully, Elizabeth A.
Abstract : Objective: To estimate age-specific abortion incidence and unintended pregnancy in Zimbabwe, and to examine differences among adolescents by marital status and residence. Design: We used a variant of the Abortion Incidence Complications Methodology, an indirect estimation approach, to estimate age-specific abortion incidence. We used three surveys: the Health Facility Survey, a census of 227 facilities that provide postabortion care (PAC); the Health Professional Survey, a purposive sample of key informants knowledgeable about abortion (n=118) and the Prospective Morbidity Survey of PAC patients (n=1002). Setting: PAC-providing health facilities in Zimbabwe. Participants: Healthcare providers in PAC-providing facilities and women presenting to facilities with postabortion complications. Primary and secondary outcome measures: The primary outcome measure was abortion incidence (in rates and ratios). The secondary outcome measure was the proportion of unintended pregnancies that end in abortion. Results: Adolescent women aged 15–19 years had the lowest abortion rate at five abortions per 1000 women aged 15–19 years compared with other age groups. Adolescents living in urban areas had a higher abortion ratio compared with adolescents in rural areas, and unmarried adolescent women had a higher abortion ratio compared with married adolescents. Unintended pregnancy levels were similar across age groups, and adolescent women had the lowest proportion of unintended pregnancies that ended in induced abortion (9%) compared with other age groups. Conclusions: This paper provides the first estimates of age-specific abortion and unintended pregnancy in Zimbabwe. Despite similar levels of unintended pregnancy across age groups, these findings suggest that adolescent women have abortions at lower rates and carry a higher proportion of unintended pregnancies to term than older women. Adolescent women are also not a homogeneous group, and youth-focused reproductive health programmes should consider the differences in experiences and barriers to care among young people that affect their ability to decide whether and when to parent.